Fingerprinting Of Water Contamination From Landfill Leachate Using 2H, 13C And 18O - Mostapa, Roslanzairi (2011)
This study presents the use of stable isotopes (2H, 18O and 13C) for the determination of δ2H–H2O, δ18O–H2O and δ13C–Dissolved Inorganic Carbon (δ13C–DIC) as a method to investigate leachate contamination in water bodies. The technique involves the collection of water samples from a municipal solid waste landfill in Perak, Malaysia. Water sampling was conducted bi-monthly for one year starting from July 2009 to June 2010. A total of 38 water samples were collected from various locations in the vicinity of the landfill. These water samples were taken from surface waters (upstream and downstream of the river, located adjacent to the landfill site, pond and leachate) and groundwater (monitoring wells). The physical parameters (pH and conductivity) and its major ions were also measured. These hydrochemical results are imperative, as it will be used in conjunction with the isotopic data. The Piper diagram plotted showed a variation for surface water (P1) and groundwater (TP6), and these water samples indicated an evolution resulting from mixing with leachates. Meanwhile, TP9 (groundwater) demonstrated a very distinct characteristic of saline water. Results for the δ2H–H2O, δ18O–H2O and δ13C–DIC ranged from +7.70‰ to –48.57‰, –0.05‰ to –7.56‰ and +10.60‰ to –23.17‰ respectively, with unique distinct isotopic signature for leachate, surface water (P1) and groundwater (TP6). However, the rivers showed no sign of leachate influence with no significant isotopic signature.